Making a case for endovascular approaches for neural recording and stimulation. (1st February 2023) - Thielen, Brianna; Xu, Huijing; Fujii, Tatsuhiro; Rangwala, Shivani D; Jiang, Wenxuan; Lin, Michelle; Kammen, Alexandra; Liu, Charles; Selvan, Pradeep; Song, Dong; Mack, William J; Meng, Ellis
Abstract: There are many electrode types for recording and stimulating neural tissue, most of which necessitate direct contact with the target tissue. These electrodes range from large, scalp electrodes which are used to non-invasively record averaged, low frequency electrical signals from large areas/volumes of the brain, to penetrating microelectrodes which are implanted directly into neural tissue and interface with one or a few neurons. With the exception of scalp electrodes (which provide very low-resolution recordings), each of these electrodes requires a highly invasive, open brain surgical procedure for implantation, which is accompanied by significant risk to the patient. To mitigate this risk, a minimally invasive endovascular approach can be used. Several types of endovascular electrodes have been developed to be delivered into the blood vessels in the brain via a standard catheterization procedure. In this review, the existing body of research on the development and application of endovascular electrodes is presented. The capabilities of each of these endovascular electrodes is compared to commonly used direct-contact electrodes to demonstrate the relative efficacy of the devices. Potential clinical applications of endovascular recording and stimulation and the advantages of endovascular versus direct-contact approaches are presented.